A contribution to the theory of optimal utilitarian income taxation - Martin Hellwig (Max Planck Institute for Research on Collective Goods, 2005)
The paper provides a new proof of the positivity of the optimal marginal income tax, in a more general model, under weaker assumptions. The analysis focusses on the (weakly) relaxed problem in which upward incentive constraints are replaced by a monotonicity condition on consumption. Without upward incentive constraints, nonnegativity of the optimal marginal income tax is straightforward; strict positivity follows from an assumption on the desirability of redistributing leisure. The resulting allocation is incentive compatible, and is optimal for the original income tax problem. The argument is the same for distributions with finitely many types and for a continuous type distribution.
Keywords: D63; H21; 330; Optimal Income Taxation; Utilitarian Welfare Maximization; Redistribution; Optimale Besteuerung; Einkommensteuer; Steuertheorie; Theorie